2013
DOI: 10.1111/j.1600-0706.2013.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Antelope mating strategies facilitate invasion of grasslands by a woody weed

Abstract: Intra and interspecifi c variation in frugivore behaviour can have important consequences for seed dispersal outcomes. However, most information comes from among-species comparisons, and within-species variation is relatively poorly understood. We examined how large intraspecifi c diff erences in the behaviour of a native disperser, blackbuck antelope Antilope cervicapra , infl uence dispersal of a woody invasive, Prosopis julifl ora , in a grassland ecosystem. Blackbuck disperse P. julifl ora seeds through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…Prosopis spreads naturally from land-rehabilitation sites through seed dispersal by stream flow and in the dung of livestock feeding on Prosopis pods (Sawal et al, 2004;Jadeja et al, 2013). Prosopis is still being planted for restoration of much degraded lands and degraded mountain ranges in the central dry zone of Myanmar (2013 plantation records of the Forest Department and the Dry Zone Greening Department).…”
Section: Introductionmentioning
confidence: 99%
“…Prosopis spreads naturally from land-rehabilitation sites through seed dispersal by stream flow and in the dung of livestock feeding on Prosopis pods (Sawal et al, 2004;Jadeja et al, 2013). Prosopis is still being planted for restoration of much degraded lands and degraded mountain ranges in the central dry zone of Myanmar (2013 plantation records of the Forest Department and the Dry Zone Greening Department).…”
Section: Introductionmentioning
confidence: 99%
“…Bulk of seeds dispersing by blackbuck through their digestive system, defecated seeds which fall on the ground and growing there naturally (Chandru et al 2020). Some of the earlier studies reported for the consumption and seed dispersal of P. juliflora in grassland habitat by Antilope cervicapra (Jadeja et al 2013;Corlett 2017;Yamato et al 2020).…”
Section: Economic Importancementioning
confidence: 97%
“…Licking is also perceptible social spectacle in blackbuck and is explicated by the female group size (Isvaran 2000;Isvaran 2005b) and mating strategy. Blackbuck use facial scent gland to mark their territory observed mostly in the days of rut development (Jadeja et al 2013).…”
Section: Territory Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While much research has been performed to optimize fecal sampling methods for carnivores [ 16 , 17 ], further optimization is necessary for social ungulates, where transect sampling methods may be inadequate to obtain sufficient sample sizes of scat [ 9 ]. Unlike carnivores, many ungulate species avoid roads [ 18 ] and do not form latrine sites (but see [ 19 , 20 ]), requiring additional effort to acquire sufficient sample sizes of scats. The deposition of scat by many herbivores may, however, be greatly influenced by the presence of social structures, such as aggregative behaviors.…”
Section: Introductionmentioning
confidence: 99%